The relationship between forgiveness and history of suicide attempt - Sansone, Randy A. (Mental health, religion & culture, 2013)
The sentiment of forgiveness in relationship to suicide attempts/completions has been mostly examined through studies of suicide notes and the experiences of survivors and therapists - not attempters. In a cross-sectional sample of 304 consecutive primary care patients, we examined sentiments about forgiveness using the Forgiveness Scale, comparing those individuals with versus without past suicide attempts. According to findings, individuals with past suicide attempts (N = 55; 19.1%) evidenced significantly lower composite scores on the Forgiveness Scale. As for individual items, compared to participants without past suicide attempts, those with past suicide attempts were significantly less believing of forgiveness by others, were less likely to forgive themselves, and to a lesser degree, were less forgiving of others. There were no between-group differences with regard to confession of wrongdoing or existential forgiveness by God. Findings may offer some salient avenues of therapeutic inquiry and endeavour in the psychological healing of individuals with past suicide attempts.